EVALUATION OF LABOR PERFORMANCE AT BATU AMPAR BATAM PORT - Nugraha, Bugi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The aim of this research was to determine the progress of loading and discharging manpower performance and factors that affect the productivity at the port that caused delays in loading and discharging at the Batu Ampar port, Batam. This research was conducted at Batu Ampar Port, Batam for 10 months, starting from August 2018 to June 2019. The obtained data sources were primary data that were directly obtained from the research place by observation and interview, also secondary data which were litteratures that are related to this research. The result of this research shows that Loading and discharging manpower activity at Batu Ampar Port Batam has not been optimal yet, this is caused by the less of employees' performance. So that caused the late loading and discharging process, in the end it caused a loss that was big enough for the company